DAMPAK STRATEGI PENGUNGKAPAN INFORMASI EMITEN TERHADAP PERUBAHAN HARGA SAHAM - SUPARTA WISADHA, I GEDE (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 3 No 2 (2008), 2008)
The purpose of this research is to empirically examine hypothesis stating that information disclosure strategy affects the changes of stock prices. This research is motivated by the occurrence of asymmetry information and conflict of interest problems. Research method is event study with period interval of 3 days before and after the date of disclosure. The population consists of 345 industry corporations listed on Indonesian Capital Market (BEI). The result using cumulative abnormal return (CAR) confirms positive results. The hypothesis testing done partially and simultaneously show that information disclosure strategy affects stock price changes significantly.
Keywords: disclosure strategy, asymmetry information, conflict of interest, abnormal return.